Perioperative Complications in Patients of Acute Cholecystitis, Early Laparoscopic Cholecystectomy versus Interval Laparoscopic Cholecystectomy; A Comparative Study - Hassan, Najmul; Khan, Shahid Mehmood; Bajwa, Khurram; Hussain, Syed Mukarram; Batool, Wajeeha; Ashraf, Imran (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the frequency of perioperative complications in patients with acute cholecystitis who undergo “early laparoscopic cholecystectomy” versus those who have “interval laparoscopic cholecystectomy”. Study Design: Quasi-experimental study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Aug 2022 to May 2023. Methodology: This study included all the patients who had acute cholecystitis and were admitted to the surgery ward for its management. Half of the patients were selected who underwent early laparoscopic cholecystectomy, while the remaining half had interval laparoscopic cholecystectomy. The frequency of perioperative complications was noted in both groups. Results: In our study, we included 50 patients (25 in group-A, who had “early laparoscopic cholecystectomy” while 25 in group-B, who had “interval laparoscopic cholecystectomy”). The mean age of the study population was 43.70±5.91 years. 18(36.00%) were male while the remaining 32(64.00%) were female. In our study, frequency of perioperative complications in group-A was injury to common bile duct 2(8.00%), biliary leak 3(12.00%), haemorrhage 4(16.00%) and conversion to open cholecystectomy 1(4.00%) while in group-B these were 0(0.00%), 1(4.00%), 2(8.00%) and 0(0.00%), respectively [with corresponding p-values of 0.149, 0.297, 0.384 and 0.312, respectively. Conclusion: Interval laparoscopic cholecystectomy is a better surgical treatment option for patients with “acute cholecystitis”.